Analysis of IL-33 gene polymorphism (rs11792633 C/T) and risk of schizophrenia - Kordi-Tamandani, Dor Mohammad (Mol Biol Res Commun, 2016)
Recently, inflammation has been found to be a significant factor in the development of Schizophrenia (SCZ). The aim of the present research was to investigate whether interleukin-33 (IL-33, OMIM: 608678) gene polymorphism (rs11792633, C/T) is associated with the development of SCZ or not. DNA was isolated from the serum of 70 patients with SCZ and 70 healthy controls. The PCR based method was used for detection of the IL-33 polymorphism. The CT (OR=0.05, 95% CI: 0.003-0.057, P<0.001) and TT (OR=0.12, 95% CI: 0.028-0.46, P<0.001) genotypes significantly decreased the risk of SCZ. Our present findings indicate that the IL-33 polymorphism associated with the risk of SCZ.